Sunteți pe pagina 1din 7
m ( BDC ) = m ( BC ) − m ( AE ) 2
m ( BDC ) = m ( BC ) − m ( AE ) 2
m ( BDC ) = m ( BC ) − m ( AE ) 2
m ( BDC ) = m ( BC ) − m ( AE ) 2

m( BDC) = m(

BC) m( AE)

2

m ( BDC ) = m ( BC ) − m ( AE ) 2 AF

AF DC

BDC

BAF

m ( BDC ) = m ( BC ) − m ( AE ) 2 AF
BAF ) = m ( BF ) = m ( BC ) − m (
BAF ) = m ( BF ) = m ( BC ) − m (
BAF ) = m ( BF ) = m ( BC ) − m (
BAF ) = m ( BF ) = m ( BC ) − m (

BAF ) = m(

BF)

= m( BC) m( FC)

BAF m(

BDC

2 2

BAF m( BDC) = m(

BC) m( FC)

EC AF m( FC) = m( AE) m( BDC) = m(

2

BC) m( AE)

2

CFB) = m(

BC) + m( AD)

m(

2

BC ) − m ( AE ) 2 CFB ) = m ( BC ) +

DE AB

CFB

CDE

CDE) = m(

CE)

= m( BC) + m( BE)

CDE m(

2 2

CFB) = m(

BC) + m( BE)

CFB

CDE m(

2

CFB) = m(

BC) + m( AD)

DE AB m( BE) = m( AD) m(

2

A, B, C, D A, B, C, D

m ( 2 CFB ) = m ( BC ) + m ( AD ) DE
ABCD m ( A ) + m ( C ) = 180 0 m (
ABCD m ( A ) + m ( C ) = 180 0 m (
ABCD m ( A ) + m ( C ) = 180 0 m (
ABCD m ( A ) + m ( C ) = 180 0 m (

ABCD m( A) + m( C) = 180 0 m( B) + m( D) = 180 0

( C ) = 180 0 m ( B ) + m ( D ) =

BAD BCD m(

BAD) =

m( BCD)

2

m( BAD)

m( BCD) = m(

= 360 0

BAD)

m(

BAD)+m( BCD) = m(

BCD)

2

2

= 180 0 ABC ADC

2 2

m( A) + m( C) = 180 0

+

ABCD A, B, C, D

ABC ADC 2 2 m ( A ) + m ( C ) = 180 0

A, B D C A, B D

ABC ADC 2 2 m ( A ) + m ( C ) = 180 0
C E F BC DC m ( BCD ) = m ( BAD ) =
C E F BC DC m ( BCD ) = m ( BAD ) =
C E F BC DC m ( BCD ) = m ( BAD ) =
C E F BC DC m ( BCD ) = m ( BAD ) =

C E F BC DC

m( BCD) =

m(

BAD) = m(

BEFD)

2

m( BAD) m( EF)

2

BEFD)

m(

BAD) + m( BCD) = m(

2

+ m( BAD) m( EF)

2

=

360 0 m( EF)

2

m( A) + m( C) = 180 0

A, B, C, D

< 180 0

m ( A ) + m ( C ) = 180 0 A, B, C, D

BCD XAD m(

BAD) + m( DAX) = 180 0 m(

BAD) +

m( BCD) = 180 0

ABCD

DBC

DAC

180 0 BCD ≡ XAD m ( BAD ) + m ( DAX ) = 180
M A BC DAC MCB ≡ ACD MBC ∼ MBC ≡ DAC M B DA
M A BC DAC MCB ≡ ACD MBC ∼ MBC ≡ DAC M B DA
M A BC DAC MCB ≡ ACD MBC ∼ MBC ≡ DAC M B DA
M A BC DAC MCB ≡ ACD MBC ∼ MBC ≡ DAC M B DA
M A BC DAC MCB ≡ ACD MBC ∼ MBC ≡ DAC M B DA

M A BC DAC MCB ≡ ACD MBC ∼ MBC ≡ DAC M B DA

M A BC

DAC MCB ACD MBC

MBC

DAC MB DA

= BC

AC

= MC

MB = AD AC · BC

DC

MCD

DC

= MC

BC AC

BCA MCD

BCA MD BA

AC · BD = AB · CD + AD · BC

= CD

CA

= MC

BC

MD = AB AC · CD

ABCD

ABCD

MBC DAC

DAC DBC

BD = BM + MD BM MD

MBC DBC M (BD)

BD = AD AC · BC

AB · CD + AD · BC

+ AB · CD AC

AC · BD =

≡ DBC M ∈ ( BD ) BD = A D AC · B C AB
AC · BD = AB · CD + AD · BC ABCD + A D
AC · BD = AB · CD + AD · BC ABCD + A D
AC · BD = AB · CD + AD · BC ABCD + A D
AC · BD = AB · CD + AD · BC ABCD + A D

AC ·BD = AB ·CD +AD ·BC ABCD

+

AD · BC

AC

AC · BD = AB · CD + AD · BC AB · CD

AC

BD =

BD = BM + MD M

(BD)

ABCD

DBC

MBC

DAC

ABC BM (M (AC)) CP (P (AB)) H AP HM BCMP

BM m( BMA) = 90 0 m( CPA) =

90 0

BM m ( BMA ) = 90 0 m ( CPA ) = 90 0 AP

AP HM m( BMA) + m( CP A) = 180 0

BMC(= 90 0 )

ABC M

BCMP

BPC

m ( CPA ) = 90 0 AP HM m ( BMA ) + m (
BC MA = MB + MC ABMC AM · BC = BM · AC +
BC MA = MB + MC ABMC AM · BC = BM · AC +
BC MA = MB + MC ABMC AM · BC = BM · AC +
BC MA = MB + MC ABMC AM · BC = BM · AC +

BC MA = MB + MC

ABMC

BC MA = MB + MC ABMC AM · BC = BM · AC + CM

AM · BC = BM · AC + CM · AB [AB] [AC] [BC] AM = MB + MC

MA = MB + MC ABMC AM · BC = BM · AC + CM ·